2014
DOI: 10.1002/ieam.1571
|View full text |Cite
|
Sign up to set email alerts
|

Critical review of public health regulations of titanium dioxide, a human food additive

Abstract: From 1916 to 2011, an estimated total of 165 050 000 metric tons of titanium dioxide (TiO2) pigment were produced worldwide. Current safety regulations on the usage of the TiO2 pigment as an inactive ingredient additive in human food are based on legislation from 1969 and are arguably outdated. This article compiles new research results to provide fresh data for potential risk reassessment. However, even after 45 years, few scientific research reports have provided truly reliable data. For example, administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(136 citation statements)
references
References 61 publications
1
130
0
5
Order By: Relevance
“…Consistently with in vitro studies, experiments in mice also showed that titanium induces increased expression of pro-inflammatory cytokines (TNFα, IL-1β and IL-6), chemokines (CCL2 and CCL3), NLPR3, ROS and RNS (Huang et al, 2015, Jovanovic, 2015, Sang et al, 2012, Warme et al, 2004, Yazdi et al, 2010.…”
Section: 1immune Response To Titaniumsupporting
confidence: 77%
“…Consistently with in vitro studies, experiments in mice also showed that titanium induces increased expression of pro-inflammatory cytokines (TNFα, IL-1β and IL-6), chemokines (CCL2 and CCL3), NLPR3, ROS and RNS (Huang et al, 2015, Jovanovic, 2015, Sang et al, 2012, Warme et al, 2004, Yazdi et al, 2010.…”
Section: 1immune Response To Titaniumsupporting
confidence: 77%
“…55 Typically, the TiO 2 ingredients utilized in the food industry as lightening agents are optimized to have particle sizes of 100-300 nanometers to increase their light scattering properties. 56 Nevertheless, these ingredients contain a range of different particle sizes and there may be a significant proportion of particles with diameters <100 nm, which can therefore be considered to be nanoparticles. 57 For example, the mean diameter of the particles in food grade TiO 2 (E171) powders obtained from several manufacturers was reported to be about 110 nm, with >36% of the particles being below 100 nm.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…56 Acute and subchronic studies of the oral toxicity of TiO 2 nanoparticles have been carried out in rodents. A single oral dose of TiO 2 nanoparticles (25, 80, or 155 nm at 5000 mg/kg body weight) resulted in their accumulation in the liver, spleen, kidney, and lung tissues of mice, and also led to hepatic injury, nephrotoxicity and myocardial damage.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…The amount of TiO2 that gets absorbed by the body is actually extremely low (Cho, Kang et al 2013;Jovanović 2015). This was first proved by detecting up to 43.2±4.6 µg/L of TiO2 in the blood of volunteers after oral ingestion of 22.9 mg of TiO2 incorporated in gelatin capsules (Böckmann, Lahl et al 2000).…”
Section: Crossing Biological Barriersmentioning
confidence: 99%